Produktivitas Peran Perempuan Dalam Peningkatan Ekonomi Keluarga Melalui Pinjaman Bank Mekar di Desa Curahmalang Kabupaten Jember (International Forum of Researchers and Lecturers, 2024)
This study was conducted to determine the role of women in increasing economic productivity in the family located in Curahmalang Village, Rambipuji District, Jember Regency. The existence of this phenomenon is due to limited access to capital or business funds to develop a business which makes people, especially women in the village, make loans to Bank Mekar. This research method uses qualitative with phenomenological research method. Data collection uses purposive sampling technique. Then, from this technique, two research data are obtained, namely primary data and secondary data. The results showed that there is a role of women in improving the family economy through loans to mekar bank in Curahmalang Village, Rambipuji District, Jember Regency.